Minimally invasive surgery versus standard posterior approach in the treatment of adolescent idiopathic scoliosis: a 2-year follow-up retrospective study - Vommaro, Francesco; Ciani, Giovanni; Cini, Chiara; Maccaferri, Bruna; Carretta, Elisa; Boriani, Luca; Martikos, Konstantinos; Scarale, Antonio; Parciante, Antonio; Leggi, Lucrezia; Griffoni, Cristiana; Gasbarrini, Alessandro (European spine journal, 2024)
Purpose This is a monocentric retrospective controlled study that compares the safety and efficacy of posterior minimally invasive surgery (MISS) to standard posterior spinal fusion (PSF) surgery in adolescent idiopathic scoliosis (AIS). Methods We retrospectively collected 111 patients with Lenke type 1–6 AIS who were treated with MIS ( n = 47) or PSF ( n = 64) between February 2019 and January 2021 with a 2-year clinical and radiological follow-up. MIS technique was applied via two midline noncontiguous skin incisions ranging from 3 to 7 cm in length, so we obtained the arthrodesis only in the exposed tract, passing the rods below the fascia, avoiding the complete muscular sparing. Values of Cobb angles degrees were collected to study the correction rate of the structural major curve. Postoperative AP direct radiography and preoperative AP direct radiography were compared with the last follow-up examination. Operative time, preoperative hemoglobin (Hb) and second postoperative day Hb, full length of hospitalization, time to achieve verticalization and time to remove the drainage were recorded. NRS medium score was assessed immediately after surgery and during the whole postoperative rehabilitation treatment to estimate pain reduction. Complications were collected postoperatively and throughout the whole follow-up period. Results There was no significant difference between the two groups in terms of radiographic and clinical features. The correction rates of the structural curve resulted to be not significantly different between MISS and PSF (64.6 ± 11.7 vs 60.9 ± 13.2, p = 0.1292) as well as for the correction rate of the secondary curve between the two compared techniques (59.1 ± 13.2 vs 59.2 ± 12.4, p = 0.9865). The two groups had comparable operative time (210 min vs 215 min). The MIS group had a significantly lower reduction of postoperative Hb in comparison with PSF group (2.8 ± 1.3 mg/dl vs 4.3 ± 1.5 mg/dl, p < 0.0001). The postoperative NRS score was lower in MIS group (1.9 ± 0.8 vs 3.3 ± 1.3). PSF group was observed to have a significantly longer period of hospitalization than MIS (5.2 ± 1.4 days vs 6.3 ± 2.9 days, p = 0.206). Complications were more frequent in PSF group rather than in MFS group. Conclusions MISS is a safe and capable alternative to PSF for AIS patients with curves < 70°, with analogue capacity of scoliosis correction and same operative time and with advantages in blood loss, length of stay and postoperative pain.